MENGEMBANGKAN POTENSI PARIWISATA DAN UMKM KECAMATAN SEMIMI KECAMATAN KENDUNG SURABAYA - Istanti, Enny; Nuroini, Indi (LPPM Universitas Bhayangkara Surabaya, 2024)
The development of tourist areas can be an alternative that is expected to encourage both economic potential and conservation efforts. Apart from developing tourism potential, the existence of UMKM cannot be eliminated or avoided from now on, because their existence is very useful in distributing community income and is able to create creativity that is in line with efforts to maintain and develop elements of local community tradition and culture. Through the Real Work Lecture Activities that we carry out, it is hoped that we can help develop the tourism potential and UMKM of the Semanggi Tourism Village.